ACCURACY ANALYSIS OF DECISION SUPPORT SYSTEM APPLICATIONS USING THE WEIGHTED PRODUCT METHOD FOR SELECTING THE BEST TEACHER - Putra, Andi; Budiarni, Rini; Kesuma, Ocha Raganata (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study evaluates the effectiveness of the Weighted Product (WP) method in improving objectivity and efficiency in the decision-making process for selecting the best teachers at SMP Cahaya Islam. The WP method was selected due to its ability to provide measurable assessments through weighted calculations on predefined attributes. Method: A web-based Decision Support System (DSS) application was developed using the WP method. The application incorporated assessment criteria, including Lesson Planning, Lesson Implementation, Learning Outcome Assessment, Training and Mentorship, Additional Duties, and Professional Development. Results: The evaluation results showed that the WP-based DSS application produced consistent and accurate assessments, achieving a 100% accuracy level compared to manual assessment methods. Additionally, the application improved objectivity, making the selection process more structured, transparent, and accountable. Novelty: This study highlights the implementation of a WP-based DSS application to enhance transparency and efficiency in teacher selection. The developed system ensures objective and effective performance assessments, contributing to improved educational quality at SMP Cahaya Islam.